Incremental value of blood-based markers of liver fibrosis in cardiovascular risk stratification - Georgiopoulos, Georgios; Athanasopoulos, Stavros; Mavraganis, Georgios; Konstantaki, Christina; Papaioannou, Maria; Delialis, Dimitrios; Angelidakis, Lasthenis; Sachse, Marco; Papoutsis, Dimitrios; Cavlan, Beyzan; Tual-Chalot, Simon; Zervas, Georgios; et al. (The journal of clinical endocrinology & metabolism, 2024)
Nonalcoholic fatty liver disease (NAFLD) with advanced liver fibrosis is associated with cardiovascular disease (CVD).This work aimed to examine if markers of vascular injury mediate the link between liver fibrosis noninvasive tests (LFNITs) and CVD events, and to compare the incremental predictive value of LFNITs over established CVD risk scores.Consecutively recruited individuals (n = 1692) with or without clinically overt coronary artery disease (CAD) from the Athens Cardiometabolic Cohort, were analyzed. Fibrosis-4 index (FIB-4), NAFLD Fibrosis score (NFS), and BARD score were evaluated for direct and indirect associations with indices of subclinical arterial injury including carotid maximal wall thickness (maxWT) and pulse wave velocity (PWV) and with a composite of major adverse cardiovascular events (MACE) that consisted of cardiac death, acute myocardial infarction, or coronary revascularization (39-month median follow-up).FIB-4 was the only LFNIT that was consistently associated with multiple markers of vascular injury, irrespective of CAD presence and after controlling for traditional risk factors, surrogates of insulin resistance, or obesity (adjusted P < .05 for all). FIB-4 was also independently associated with CAD presence (adjusted odds ratio [OR] 6.55; 3.48-12.3; P < .001). Increased FIB-4 greater than 2.67 was incrementally associated with an increased risk for MACE (OR [95% CI] 2.00 [1.12-3.55], ΔAUC [95% CI] 0.014 [0.002-0.026]). These associations were mediated by maxWT rather than PWV. Only FIB-4 (>3.25) was independently and incrementally associated with all-cause mortality (adjusted P < 0.05).In a cardiometabolically diverse population, the incremental associations of LFNITs with CVD outcomes were mediated by atherosclerotic burden rather than arterial stiffening. FIB-4 consistently demonstrated associations with all study end points. These findings provide mechanistic insights and support the clinical applicability of FIB-4 in CVD prevention.
Online veröffentlicht: 11 September 2024
Gesehen am 14.01.2025